Evaluation of antitrypanosomal activity of bisindole alkaloid, ochrolifuanine from Dyera costulata (Miq.) Hook.f / Norhayati Ismail - Norhayati , Ismail (2019)
Human African Trypanosomiasis (HAT) is a neglected tropical disease which can be fatal if left untreated. The search has been ongoing to explore additional or alternative remedies from natural products which have great potential to treat the disease since current drugs treatment are very limited due to resistance and side effects to patients. The aim of this study was to search for potential antitrypanosomal compound candidate from Dyera costulata (Miq.) Hook.f (locally known as jelutong) leaves. In this study, an antitrypanosomal active compound was isolated from the active methanolic extract of D. costulata leaves by using bioassay-guided isolation and chromatographic techniques. The compound identified as bisindole alkaloid ochrolifuanine using Nuclear Magnetic Resonance (NMR) and Mass Spectrum (MS) as well as by comparison with reported data. The in vitro inhibitory activity of extract and fraction samples against Trypanosoma brucei brucei strain BS221 was tested using Alamar Blue assay. Ochrolifuanine showed potent antitrypanosomal activity with IC50 value 0.05 ± 0.01 μg/ml and high selectivity towards the trypanosome cells (Selectivity Index, SI = 52). Since apoptosis plays an important role in cell density regulation in the parasite, the effect of ochrolifuanine in apoptosis induction was investigated. Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) assay was used to observe the effect of ochrolifuanine on apoptotic DNA fragmentation in T. b. Brucei cells treated with ochrolifuanine. Ochrolifuanine was shown to induce an apoptotic DNA fragmentation in trypanosome cells in a dose- and time-dependent manner. Trypanosome cells treated with 0.05 μg/ml concentration of ochrolifuanine exhibited early apoptosis and more than 50% apoptotic cells were detected in as early as 6 hours of incubation. Additional study on measurement of DNA content in trypanosome parasites was carried out using flow cytometry. In 24 hour observations, treatment of cells with 0.025 and 0.05 μg/ml of ochrolifuanine arrested the growth of T. b. brucei at two different phases (G0/G1 and in S phases). While at the highest dose treatment of 0.10 μg/ml of ochrolifuanine, blockage of cell progression at the G2/M phase in T. b. brucei cell cycle was observed. These results demonstrated that ochrolifuanine displayed strong antitrypanosomal effect on T. b. brucei by inducing apoptosis and causing arrest of parasite cells at different growth phases. This study reports for the first time on the antitrypanosomal activity of ochrolifuanine from D. costulata leaves. Hence, ochrolifuanine is a potential candidate for the discovery of novel therapeutic drugs to treat trypanosomiasis disease.